Procesos administrativos de la empresa de Transporte de Carga Pesada Cotrarioba S.A., de la ciudad de Babahoyo durante el periodo 2023. - Cruz Escobar, Kevin David (2024)
The case study conducted at the Heavy Cargo Transport Company Río Babahoyo S.A. Cotrarioba focused on evaluating the efficiency of its administrative processes during the 2023 period to identify areas for improvement. This company was founded in 2013, is dedicated to road freight transport and has 125 partners and 3 administrative staff. The company faced significant problems in its planning, organization, direction and control processes, which affected its efficiency and profitability. The objective of the research was to examine how administrative processes influenced the company's performance and to detect the deficiencies present at each stage of the administrative process. To achieve this, a mixed methodological approach was used that combined qualitative and quantitative techniques. Interviews were conducted with the manager, president and secretary to obtain perspectives on internal communication, planning and document management. In addition, financial indicators were analyzed to evaluate the company's profitability and performance. The study sought to identify and understand deficiencies in internal communication, inadequate planning, disorganized documentation, and poor financial control. Based on these findings, corrective actions were proposed to optimize administrative management. Recommendations include the creation of a strategic plan for continuous improvement that establishes a committee to oversee corrective actions. These actions were aimed at improving administrative efficiency, reducing costs, and strengthening the organizational structure, with the goal of ensuring sustainable growth and improving profitability.